PERANAN LEMBAGA PENDIDIKAN MAJELIS MUSYAWAROH FATHUL FALAH DALAM MENJAMIN MUTU DAN KOMPETENSI SANTRI KILATAN PUTRA PONDOK PESANTREN FATHUL‘ULUM KWAGEAN KEPUNG - ali muchasan; M Syarif (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2021)
To improve and ensure the quality and competence of students, it is necessary for boarding school to form an organizational institution that is tasked with maximally managing, organizing and improving the quality of education for flash students. This research aims to determine the role and influence of the fathul falah deliberative assembly educational institutions in ensuring the quality and competence of the male students of fathul ‘ulum boarding school kwagean.This study uses mixed methods. Based on the results of the calculation of 10 questions related to the Role of the Fathul Falah deliberative assembly Educational Institution in Ensuring the Quality and Competence of the male flash students FATHUL ULUM BOARDING SCHOOL KWAGEAN towards 22 male flash student respondents, included in the "Quit Successfull" category. This can be seen from the results of the calculation of the average value of all respondents, namely 39.4, which is included in the "Enough Agree" category.